35. EVALUATING THE RESULT LINE 1 OF TREATMENT NON SMALL CELL LUNG CANCER PATIENTS STAGE IV HABOR EGFR MUTATION BY OSIMERTINIB AT NATIONAL LUNG HOSPITAL FROM 2019 TO 2022 (Vietnam Journal of Community Medicine, 2024)
Objectives: (1) To evaluate the rate of response and the period time of progression-free survival. (2) To evaluate side effects of Osimertinib.Methods: Cross-sectional descriptive study 31 adenonocarcinoma lung cancer harboring EGFR mutations patients at National Lung Hospital, from December 2019 to August 2023.Results: The mean of age is : 63,42 ± 9,36 age, the youngest is 40 and the oldest is 85 age, female/male is 1,07/1, the most common symptom is chest pain with 26 patients. The most common location metastasis is pleural with 18 patinents. EGFR mutations at exon 19 is the common than at exon 21 with rate 19/11, one patient habor T790M mutation. Overall response rate (ORR) is 70,9 % with 61,3% is partial response. The mean progression-free survival is 20,70 ± 3,32 months, median PFS is 15,67 months with minimum is 3,19 months and maximum is 44,16 months. The most common treatment accompanied is Zoledronic acid with 11 patients. Recording side effects, rash on skin is the most common with rate is 48,4 %, most of them are grade I. Side effects with increasing aspartat transaminase and alanin transaminase grade I with 8 patients (25,8%) and all side effects: No patients with grade III or grade IV.Conclusion: Treatment by target drug as Osimertinib with patients adenocarcinoma lung cancerstage IV harboring EGFR mutations has high overall response rate : 70,9%, median progression-free survival is 15,67 months. Side effects are often mild. So with adenocarcinoma lung cancer harboring EGFR mutations, we should treatment by Osimertinib, special in old patients, who has not good performance status, can not treatment with chemotherapy.
Keywords: Osimertinib, tagrisso lung cancer, EGFR mutations, progression-free survival, side effects, overall survival.